Successful rivaroxaban and doxycycline therapy for Mycoplasma pneumonia with pulmonary embolism in children: a case report - Xiaoqian, Fang; Hemin, Lu (Frontiers in Pediatrics, 2025)
The mortality of pulmonary embolism in children is high, and there is no standardized treatment protocol. We present a case of successful treatment of Mycoplasma pneumoniae (M pneumoniae) with pulmonary embolism in a child using rivaroxaban and doxycycline, thereby exploring a more appropriate treatment option. A 10-year-old male presented with fever, cough, and chest pain as the main symptoms. M pneumoniae polymerase chain reaction of bronchoalveolar lavage fluid was positive, and computed tomography angiography indicated pulmonary embolism. Azithromycin, doxycycline, and piperacillin-tazobactam were administered sequentially for infection control, while methylprednisolone was given to control inflammation and heparin and rivaroxaban for sequential treatment, resulting in a satisfactory recovery.